Transição cultural : divergências diante da formação de uma nova identidade : estudo de caso da Companhia Siderúrgica de Tubarão - CST - Lugon, Carlos Wilson (2001)
The employees' partlclpation in the cultural transltIon process occurred in Companhia Siderúrgica de Tubarão (CST) was helpful in the identification of the group of measures that started to be managed in order to be established in the run of the control assumption. The company, in order to acquire proper features, had to change prior values, behaviors and identities through strategies shared by ali the organization members, thus, creating a new culture. The CST was seen as a company controlling and coordinating a group of people. It counted on vertical hierarchical leveis, departments and authority relations. It was neve r taken into account that the company could have its own personality, like each person that worked there. Before getting through this cultural transition process, that extremely changed its values, the company had a dominating culture, with a centralized administration. This way, it influenced the conduct of ali its members, in a controlling environment. When the company realized the necessity of investments in cultural changing programs, in order to eliminate the pathologies and disfunctions that were hitting its business structure, causing damage to productivity and to the quality of the results, it condensed energies in one direction implementing the participation of ali its leaderships as implementing and multiplier elements to orientate and facilitate the achievement of its goals. Trying to understand better the influences suffered by the changes brought by globalization and privatization, some theorical and operational concepts of culture and identity were developed in this study, mainly in the first chapters. In the research extension, several aspects of this complex anthropological and sociological concept of culture were managed, such as affectiveness, cognitive process, valuation process and everything that could be related to or that give elligibility to this concept and to the phenomenon this concept will consist in.